Abandoning historical conflict? : Former political prisoners and reconciliation in Northern Ireland /: Former political prisoners and reconciliation in Northern Ireland. (2013) - Shirlow, Peter; Tonge, Jon; McAuley, James; McGlynn, Catherine
No abstract available